Late Onset of Pancreatic Metastases from Renal Cell Carcinoma. A Case Report - Janevska, V; Shumkovski, Aleksandar; Nikolova, Dafina; Asani, Learta; Pandilov, Stefan; Karanfilovski, Vlatko (Walter de Gruyter GmbH / Macedonian Academy of Sciences and Arts, 2020)
Metastasis of renal cell carcinoma (RCC) to the pancreas is a rare entity accounting only 0.25-3% of all pancreatic tumors. We present a rare case of isolated three focal pancreatic metastases from RCC, occurring 15 years after the left nephrectomy. The majority of the pancreatic metastases are asymptomatic, as it was in case of our patient excluding the weight loss for the last three months. We demonstrate the importance of the medical history, radiological examinations, histological and immunohistochemical analysis in making a definitive diagnosis.